Artificial intelligence decision-making in mobile health. (18th October 2019) - Menictas, Marianne; Rabbi, Mashfiqui; Klasnja, Predrag; Murphy, Susan
Abstract : It is likely that you or someone you know is affected by a chronic health condition. For example, a staggering six in 10 adults in the USA are currently suffering from a chronic disease (National Center for Chronic Disease Prevention and Health Promotion, 2019). Unfortunately, chronic conditions are not treatable overnight, but they can often be improved by regular incorporation of preventative behaviours (e.g., taking medication, healthy sleeping habits, being physically active, healthy eating, etc.). However, due to the many contingencies that arise in our lives, regular incorporation of healthy behaviours is difficult, and often when we need help in enacting these behaviours, support from clinical professionals is not available.